Perancangan Aplikasi Enkripsi dan Dekripsi Gambar Cetak Biru Pada PT. Patco Elektronik Teknologi Menggunakan Algoritma RSA Berbasis Android - Arafat Bagoes Setyawan; Muhammad Khaerudin; siti setiawati (NUANSA INFORMATIKA, 2024)
PT. Patco Elektronik Teknologi, a leading company in the Electronics industry, urgently needs to enhance the security of blueprint mold data in its Moldshop division. The process of mold repair using CNC machines requires secure access to the company's standard blueprint drawings. Hence, this study aims to develop an Android-based application for encrypting and decrypting blueprint images using the Rivest Shamir Adleman algorithm. It also addresses challenges such as budget constraints, Android device availability, and data security. The method chosen, Rivest Shamir Adleman, is renowned for its asymmetric cryptography and will be implemented in the Android application for securing blueprint images. The research successfully resulted in the creation, implementation, and testing of the Rivest Shamir Adleman Android application. Testing demonstrated that the program can efficiently encrypt and decrypt blueprint images, with encryption averaging 4 to 15 seconds and decryption 2 to 5 seconds using this method. By employing Rivest Shamir Adleman, the application ensures high-level security for blueprint image files.